Who is undermining employee involvement in postsocialist supervisory boards? National, European and international forces in the revision of Hungarian company law - Arjan Vliegenthart (Journal for East European Management Studies, 2009)
This article explores regulatory developments with regard to employee representation in post-socialist corporate governance systems of Central Europe. It sets out to weigh the applicability of different theories on postsocialist industrial relations that focus on domestic, European and international forces. It pays special attention to the Hungarian case and studies regulatory developments in the early 2000s, with a focus on the third postsocialist Company Law of 2006. The article argues that the law reform undermines effective employee representation in postsocialist corporate governance systems. It concludes that these developments can only be adequately understood as the result of the interplay between various social forces at the national, European and international level. – – Dieser Beitrag erforscht die regulativen Entwicklungen hinsichtlich der Arbeitnehmervertretung im Kontext postsozialistischer Corporate-Governance- Systeme in Mitteleuropa. Er beginnt mit der Überprüfung der Anwendbarkeit von verschiedenen Theorien, mit Fokus auf inländische, europäische und internationale Kräfte, auf die postsozialistischen industriellen Beziehungen. Es wird speziell der ungarischen Fall untersucht, wobei die regulativen Entwicklungen zu Beginn dieses Jahrzehnts, und besonders das dritte postsozialistische Unternehmensrecht von 2006 im Zentrum der Betrachtung stehen. Es wird argumentiert, dass die Gesetzesreform eine wirksame Arbeitnehmervertretung in postsozialistischen Corporate-Governance- Systemen unterminiert. Zusammenfassend kann festegestellt werden, dass diese Entwicklungen nur als das Ergebnis des Zusammenspiels zwischen verschiedenen sozialen Kräften auf der nationalen, europäischen und internationalen Ebenen adäquat verstanden werden können.
Keywords: 650; Corporate governance; supervisory boards; company law; Hungary; postsocialism; transnationalism